Candidate locus analysis of the TERT–CLPTM1L cancer risk region on chromosome 5p15 identifies multiple independent variants associated with endometrial cancer risk - Carvajal-Carmona, L.G (Springer Verlag, 2020)
10.1007/s00439-014-1515-4